Sustainable and competitive nightlife district? – Management of overtourism in Budapest - Pinke-Sziva, Ivett; Smith, Melanie; Berezvai, Zombor; Coronel Padilla, Monica (Marketing & Menedzsment, 2020)
THE AIMS OF THE PAPER The main objective of the paper is to answer a controversial question: How can a district that is inhabited by local residents, but is popular for touristsparticularly during nightlife, be sustainable in a city? This question has become crucial in Budapest, where local residents are demonstrating over the impacts of party tourism. In this context, the study aims to find out creative product development ideas to deal with the mass tourism activities. METHODOLOGY Data collection took place in District VII and comprised two surveys: one in Hungarian conducted to local residents and Hungarian visitors; and one in English conducted to foreign tourists. Additionally, semi-structured interviews were carried out in Budapest to experts in the field of tourism working in different areas. The gathered data was analyzed through closed coding. MOST IMPORTANT RESULTS In total, 574 questionnaires in Hungarian and 361 questionnaires in English were analyzed, together with 40 interviews. The findings show that tourists feel mainly attracted by the atmosphere and the ruin pubs of the nigh-time district. This phenomenon has led to huge concentrations of tourists and general concerns about cleanliness and safe. New product development integrating peripheral attractions to target specific segments of tourists is seen as a possible solution, as well as pricing strategies or the reduction of accommodation, transport and visitors’ carrying capacity. RECOMMENDATIONS The paper introduces definitions of the night-time economy and approaches to sustainable management of tourism in cities, as well as an analysis of the impacts of overtourism not only in District VII but in Budapest. The study identifies methods of coping with negative impacts of tourism and offers solutions to the management of overtourism. Based on the results, concrete visitor management solutions can be created to support widening the area of the tourism flow in Budapest and offer authentic experiences outside the core tourism area.